Factores asociados a la retinopatía en diabéticos de 40 a 79 años, desde una perspectiva familiar, Loja. 2016. - Zhunaula Carrión, Sonia Beatriz (2017)
The study objective was to determine protection and risk factors for the retinopathy apparition in diabetes patients aged 40 to 79 from Loja city, from a familiar functionality perspective. The study is a prospective, descriptive, cross-sectional, case-control type. 500 type 2 diabetic patients were studied, in which the association of factors considered as protection or risk into diabetic retinopathy apparition was studied. Considering of greater importance the association of modifiable risk factors such as hyperglycemia with HbA1c, lipid profile and blood pressure, as well, age, sex, time of evolution of diabetes, alcohol, tobacco, treatment, other comorbidities, depression, stress, anxiety, family functionality, family support and adherence to treatment were analyzed. Descriptive statistics, chi2 and odds ratio were used, with a level of significance of 0.05. There were more risk factors than protection for diabetic retinopathy with statistical significance p <0.05. Laboratory parameters in 60% in diabetic people were not controlled, nor was blood pressure presented in 62.6% in patients with diabetic decompensation. Familiar function and support, and adherence to treatment were not significant, p> 0.05, however, 31.8% of diabetics had familial dysfunction; 61.6% patients did not have family support, and 57.4% were not adherent to treatment, which was associated more frequently with poor control of their disease. Concluding, risk factors that intervened in this study are consistent with those reported in the reviewed literature and with the results of other studies related, which are of great importance because their association to the early development of retinopathy in diabetic patients poorly controlled. Keywords: mellitus diabetes, familiar characteristics, risk factors, arterial hypertension, familiar dynamic, non- proliferative retinopathy.